The geographical distribution, trophic modes, and host preferences of Fomitopsis pinicola in Central Europe: a comprehensive review - Gáper Ján; Gáperová Svetlana; Pristaš Peter; Šebesta Martin; Kollárová Patrícia; Gallay Igor; Slobodník Branko (Central European Forestry Journal)
Fomitopsis pinicola [Sw.] P. Karst. is one of the most common wood-decaying macrofungi which is adapted to growth under different environmental conditions, but little is known about its intraspecific variation in spatial distribution, function and substrate specificity in different habitats. To understand how the geographical distribution, trophic mode and host specificity of this fungus vary across different habitat categories, we analysed its habitat and trophic preferences using Slovakia (Central Europe) as an example. For this purpose we studied and compared the archived material (fungarium items and field notes) from 1954 to present, obtained from own collections and external sources. The occurrence of F. pinicola in forests and quasi-natural habitats is related to the distribution of Norway spruce. Contrariwise, sites with its presence in public urban spaces are scattered throughout the whole territory of Slovakia. The occurrence of F. pinicola as a saprotroph is highest in forests and lowest in public urban spaces, where it accounts for 90.1% and 27.7% of the total number of records, respectively. F. pinicola was also shown as an important pathotroph of broadleaves in public urban spaces, where pathotrophy concerns as high as 72.3% of relevant records. Prunus species are the most frequently infested woody plants, accounting for 81.3% of these records. In silico analysis of available F. pinicola ITS sequences indicates its genetic homogeneity in Central Europe and the adjacent regions. Thus, the observed differences in trophic modes and host preferences of F. pinicola from different habitats cannot be explained by its intraspecific genetic variability.